A Member of the Arabidopsis Mitochondrial Transcription Termination Factor Family Is Required for Maturation of Chloroplast Transfer RNAIle(GAU). Issue 1 (7th July 2015) - Romani, Isidora; Manavski, Nikolay; Morosetti, Arianna; Tadini, Luca; Maier, Swetlana; Kühn, Kristina; Ruwe, Hannes; Schmitz-Linneweber, Christian; Wanner, Gerhard; Leister, Dario; Kleine, Tatjana
Abstract : The product of a termination factor promotes maturation of a transfer RNA in Arabidopsis plastids. Abstract: Plastid gene expression is crucial for organelle function, but the factors that control it are still largely unclear. Members of the so-called mitochondrial transcription termination factor (mTERF) family are found in metazoans and plants and regulate organellar gene expression at different levels. Arabidopsis ( Arabidopsis thaliana ) mTERF6 is localized in chloroplasts and mitochondria, and its knockout perturbs plastid development and results in seedling lethality. In the leaky mterf6-1 mutant, a defect in photosynthesis is associated with reduced levels of photosystem subunits, although corresponding messenger RNA levels are unaffected, whereas translational capacity and maturation of chloroplast ribosomal RNAs (rRNA s) are perturbed in mterf6-1 mutants. Bacterial one-hybrid screening, electrophoretic mobility shift assays, and coimmunoprecipitation experiments reveal a specific interaction between mTERF6 and an RNA sequence in the chloroplast isoleucine transfer RNA gene ( trnI.2 ) located in the rRNA operon. In vitro, recombinant mTERF6 bound to its plastid DNA target site can terminate transcription. At present, it is unclear whether disturbed rRNA maturation is a primary or secondary defect. However, it is clear that mTERF6 is required for the maturation of trnI.2 . This points to an additional function of mTERFs.